Penguatan Peran Guru dalam Kesehatan Mental Siswa melalui Pelatihan Coping Strategy di SDN 13 Konda - Muh. Yasa; La Ode Ahmad Yusran; Erwin Eka Saputra (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
Elementary school students' mental health is a fundamental aspect in supporting successful learning, social development, and personality development. However, in many elementary schools, attention to this aspect is still not optimal, and teachers tend to focus solely on academic achievement. This Community Service (PkM) activity aims to strengthen the role of teachers in supporting student mental health through mental health-based coping strategy training at SDN 13 Konda. The implementation method uses a participatory and collaborative approach with four main stages: preparation, training, mentoring, and evaluation. The training stage is carried out in the form of an interactive workshop that equips teachers with an understanding of the concept of children's mental health, types of student stress, the role of teachers as psychological counselors, and adaptive coping techniques. The mentoring stage is carried out through classroom observations, reflective discussions, and consultations to ensure contextual implementation of strategies. Evaluation is carried out through questionnaires, observations, and teacher reflections. The results of the activity show a significant increase in teachers' understanding of student mental health, from an average pre-test of 49.1% to a post-test of 86.8%. Furthermore, teachers' skills in implementing coping strategies in the classroom also significantly improved, as evidenced by the use of empathetic language, positive conflict management, and providing students with space to express their emotions. Evaluations revealed a shift in teachers' attitudes, leading to greater sensitivity, confidence, and support for students' emotional well-being. This activity demonstrates the effectiveness of mental health-based coping strategy training in strengthening teachers' roles and creating a psychologically healthy learning environment in elementary schools.